“Speak Up!” Investigating U.S. professional sports teams' #BlackLivesMatter statements - Kwak, Dae Hee; Pradhan, Sean; Chen, Zhjing (Frontiers in Sports and Active Living, 2023)
George Floyd's death caused by police brutality fueled a wave of the Black Lives Matter (BLM) movement both nationally and globally. Almost every professional sports team in the United States released a statement pertaining to racial inequality and social injustice. The current study investigated the content and word counts of the BLM statements posted on Twitter by all teams across the four major men's professional sports leagues: Major League Baseball (MLB), National Basketball Association (NBA), National Football League (NFL), and National Hockey League (NHL). Based on a series of text analyses, we found differences in both the content and word counts of statements put forth by each league. Notably, compared to teams in other leagues, NFL teams avoided negative sentiment words (e.g., by not using words like “racism”) and utilized more action-oriented terms like “support”, “listen”, and “conversation” in their statements. Practical implications and future directions for research are discussed.